Mengulik Peran Pelaku UMKM Perempuan Dalam Adopsi Inovasi Digital - Parlyna, Afiane; Girsang, Lasmery RM (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
MSME entrepreneurs play an important role in efforts to improve the local economy. In particular, women often become MSME leaders. Digital innovation is key to expanding reach, increasing efficiency, and creating new opportunities. This study aims to explore the process of adopting digital innovation by female Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This study uses a qualitative approach and a post-positivism paradigm to understand the factors that influence decisions to adopt digital technology, as well as the social and economic impacts of such adoption. Data were collected through interviews with three female MSME informants from Jakarta and Bekasi using the Technology Acceptance Model (TAM) theory, Miles Huberman data analysis techniques and data validity testing using the triangulation method. The results of the study indicate that factors such as education, technological skills, government support, and access to resources play an important role in influencing the adoption of digital technology. In addition, the adoption of digital technology has been shown to increase operational efficiency, expand access to markets, and empower female MSMEs economically and socially.